Performance management in small itallian non-profits - Bruni, Francesca (2020)
This paper aims at investigating performance management in the context of small non-profits in Italy. The research was based on a small charity in Rome that deals with social inclusion of minors. The analysis was undertaken through two rounds of interviews and by having access to the non-profit’s relevant documents. The research’s results have shown a strong altruistic drive and a lack of formality in performance management practices. Making a clear connection between performance management and its potential benefits to the non-profit’s cause is crucial to favour the adoption of this practice and its utilisation over time.